The multidrug-resistant tuberculosis threat: old problems and new solutions - Sotgiu, Giovanni; D’Ambrosio, Lia; Centis, Rosella; Mura, Ida; Castiglia, Paolo; Spanevello, Antonio; Migliori, Giovanni Battista (Journal of Thoracic Disease, 2015)
With more than 1 million deaths and 9 million estimated incident cases in 2013 tuberculosis represents one of the top clinical and public health priorities worldwide (1).